IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL DALAM PENGABDIAN MASYARAKAT MELALUI SEMINAR BEDAH BUKU SECARA VIRTUAL ZOOM MEETING - Khaeruman, Khaeruman; Tabroni, Tabroni; Mukhlis, Ahmad; Suflani, Suflani; Wiguna, Wahyu; Bahits, Abdul (Yayasan Education and Social Center, 2024)
The community service activity with the title “Implementation of Transformational Leadership in Community Service through a Virtual Zoom Meeting Book Review Seminar” succeeded in achieving positive results. This virtual seminar was attended by 100 participants who showed active involvement and high enthusiasm in the question and answer and discussion sessions. The speaker delivered material of excellent quality, in participant assessment. The use of Zoom Meetings has proven effective in facilitating interaction and accessibility. The application of transformational leadership creates an inspiring seminar atmosphere, increasing active participation and involvement of participants. Recommendations for future activities include extending discussion time and improving interactive technology for a more immersive experience. This seminar made a significant contribution to the development of participants' knowledge and skills and became an effective model for future community service activities